Neurological symptoms in individuals with fibrodysplasia ossificans progressiva - Kitterman, Joseph A. (2012)
Fibrodysplasia ossificans progressiva (FOP), a rare, disabling condition caused by gain-of-function mutations of a bone morphogenetic protein (BMP) type I receptor, leads to episodes of heterotopic ossification and resultant immobility. Neurological problems have not been associated with FOP, but neurological symptoms are commonly reported by FOP patients. To determine the prevalence of neurological symptoms and their characteristics in individuals with FOP, we conducted a survey of the 470 patient members of the International FOP Association (IFOPA) using a questionnaire about neurological symptoms. There were 168 responses (105 females, 63 males; age 1.5–68 years) from 30 countries representing 36 % of IFOPA members. Chronic neurological symptoms were reported by 86 (51 %). Prevalence of neuropathic pain (NP) was significantly increased (P < 0.001) compared to the general population, and tenfold more common in females (15 %) than males (1.6 %). Of those with NP, 94 % reported other sensory abnormalities. Prevalence of recurrent severe headaches (HA) (26 %) was similar to that in the general population, but prevalence in females with FOP (36 %) was almost fourfold greater than in males. Prevalence of NP, HA, and other sensory abnormalities was substantially higher in post-pubertal females; 33 % reported symptoms worsened during menstrual periods. Worsening of neurological symptoms during FOP flare-ups was reported by 23 %. Three patients with FOP (1.8 %) reported myoclonus, a prevalence much greater than reported in the general population (P < 0.001). Our worldwide survey indicates that neurological symptoms are common in FOP. We speculate that these symptoms are related to effects of dysregulated BMP signaling on the central and/or peripheral nervous systems.